SIFAT FISIK KUALITAS SUSU KAMBING PERANAKAN ETAWA LAKTASI I—IV DI DESA SUNGAI LANGKA KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Disa, Putra Rama; Husni, Ali; Sulastri, Sulastri (Jurnal Riset dan Inovasi Peternakan, 2017)
The purpose of study is to know that physical quality of milk from Crossbreed Ettawa goats lactation period I—IV, those were organoleptic test, specific gravity test, and pH test in Sungai Langka Village Gedong Tataan Subdistrict Pesawaran District. This research was conducted method of purposive sampling with goat milk sampling as much as 250 ml on each lactation period I--IV and livestock recording data using questionnaire. Steps in this study begin from sampling through the milking process on each 15 Crossbreed Ettawa goats, followed by organoleptic test, specific gravity test, and pH test. The results of research, showed that quality milk which include organoleptic test in 1st lactation--4th lactation were color (white to yellowish white; white to yellowish white; white to yellowish white; and white yellowish), odor (Unpleasant to savory; Unpleasant to savory; Unpleasant to savory; savory), consistency (thin to slightly thickened; very thin to slightly thickened; thin to slightly thickened; and somewhat lumpy), taste (very bad to awful; very uncomfortable until a little tastier; very bad to awful; and tasty), receptivity (do not like to like; do not like to like; do not like to like; and like). pH test in 1st lactation--4th lactation that is 6,60; 6,59; 6,62; 6,54. Specific gravity test in 1st lactation--4th lactation that is 1,0480; 1,0533; 1,0531; 1,0525.  Keywords : Physical Quality of Milk, Lactation Period I--IV, Crossbreed Ettawa, Sungai Langka Village